2011
DOI: 10.1103/physreva.84.052513
|View full text |Cite
|
Sign up to set email alerts
|

Finite-size effects and nonadditivity in the van der Waals interaction

Abstract: We obtain analytically the exact nonretarded dispersive interaction energy between an atom and a perfectly conducting disk. We consider the atom in the symmetry axis of the disk and assume that the atom is predominantly polarizable in the direction of this axis. For this situation we discuss the finite-size effects on the corresponding interaction energy. We follow the recent procedure introduced by Eberlein and Zietal together with the old and powerful Sommerfeld's image method for nontrivial geometries. For … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…where f (r) must assume the unit value for points belonging to the surface of the sphere, in order to satisfy equation (54). Using the fact that the Green function must be symmetric 68 by the exchange r ←→ r ′ , and since f (r) = 1 for |r| = R, we are led to the result…”
Section: Let Us Computementioning
confidence: 99%
“…where f (r) must assume the unit value for points belonging to the surface of the sphere, in order to satisfy equation (54). Using the fact that the Green function must be symmetric 68 by the exchange r ←→ r ′ , and since f (r) = 1 for |r| = R, we are led to the result…”
Section: Let Us Computementioning
confidence: 99%
“…This paper considers a Riemann space consisting of two copies of R 3 connected by a flat circular branch disk and computes the potential generated by a point charge located in the first R 3 . More recently, Riemann spaces have been considered in [32][33][34][35]. It can be shown that Sommerfeld's solution with a straight branch line and Hobson's solution with a circular branch loop can be related by an inversion transformation, see appendix D.…”
Section: Analytic Solutionmentioning
confidence: 99%
“…A relevant example is that of an atom interacting with an infinite plane with a circular aperture, which leads to repulsion as shown by Levin et al [2]. In a recent paper [17], we treated this problem by Sommerfeld's image method and obtained an analytical result for the corresponding interaction energy of this system. Our results agree with those previously obtained by Eberlein and Zietal [5].…”
Section: Other Non-trivial Applicationsmentioning
confidence: 99%
“…In this connection, we would like to mention particularly the possibility of studying finite size effects and, in some cases, non-additivity effects involving complemetary surfaces. In the latter case, the complementary geometries of an atom-disk system and the system constituted by an atom and a plane with a circular aperture was studied in [ [17]], where a surprising result was found, namely: that there exists a distance between the atom and the center of the aperture for which the non-additivity effects vanish. The authors believe this result may occur in other systems involving complementary surfaces.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation